Acinetobacter lactucae Strain QL-1, a Novel Quorum Quenching Candidate Against Bacterial Pathogen Xanthomonas campestris pv. campestris - Tian Ye; Tian Ye; Tian Zhou; Tian Zhou; Xinghui Fan; Xinghui Fan; Pankaj Bhatt; Pankaj Bhatt; Lianhui Zhang; Lianhui Zhang; Shaohua Chen; Shaohua Chen (Frontiers in Microbiology, 2019)
Quorum sensing (QS) is a cell–cell communication mechanism among bacterial populations that is regulated through gene expression in response to cell density. The pathogenicity of Xanthomonas campestris pv. campestris (Xcc) is modulated by the diffusible signal factor (DSF)-mediated QS system. DSF is widely conserved in a variety of gram-negative bacterial pathogens. In this study, DSF-degrading bacteria and their enzymes were thoroughly explored as a biocontrol agent against Xcc. The results indicated that a novel DSF-degrading bacterium, Acinetobacter lactucae QL-1, effectively attenuated Xcc virulence through quorum quenching. Lab-based experiments indicated that plants inoculated with QL-1 and Xcc had less tissue decay than those inoculated with Xcc alone. Co-inoculation of strains Xcc and QL-1 significantly reduced the incidence and severity of disease in plants. Similarly, the application of crude enzymes of strain QL-1 substantially reduced the disease severity caused by Xcc. The results showed that strain QL-1 and its enzymes possess promising potential, which could be further investigated to better protect plants from DSF-dependent pathogens.